Study on capacity analytical model for multi-channel wireless sensor networks - WANG Ming-fei1; CI Lin-lin1; ZHAN Ping2; XU Yong-jun3 (Tongxin xuebao)
An ideal packets pipeline operation scheme was used to set up the path-oriented capacity analytical model in single user multi-channel network. Then, through analyzing the essence of resource competition in multi-channel net- works, the resource constraint model of node contention domain was constructed. Furthermore, the network capacity analytical model in multi-user multi-channel network was set up based on mathematical programming. The centralized and distributed computing methods and applications are studied. The model can describe the path capacity, the network capacity, and the contention relation of the flows in multi-hop multi-channel network. The model is simple, and it can di- rect the network deployment and the design of network protocols.